Implementation of the Tomohon City Social Service Basic Food Program - Rapar, Inrytha Vanda; Tulusan, Femmy M. G.; Tampongangoy, Deysi L. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Poverty is a very important problem to solve. The Covid 19 pandemic that hit the world, including Indonesia, adds to the long record of efforts to eradicate poverty and fulfill basic needs for the community. One of the programs carried out by the government is the distribution of nine basic necessities for the community. Tomohoan City is one of fifteen districts/cities in North Sulawesi Province which also implements a basic food cash assistance program for the poor. The policies that form the basis for its implementation are Presidential Regulation Number 96 of 2015, Presidential Regulation No. 63 of 2017, Ministerial Regulation Domestic Affairs Number 32 of 2011 and Decree of the Minister of Social Affairs of the Republic of Indonesia No.146/HUK/2013. The implementation of this program is closely related to aspects of the policies implemented, target groups, implementing organizations and environmental factors. This research was conducted to explain the implementation of the basic food program carried out by the Tomohon City Social Service. The research design used is qualitative. The research findings show that the implementation of the basic food program carried out by the Tomohon City Social Service in alleviating poverty has been running from the aspect of idealized policy and the policy environment, but has not been appropriate in terms of data on the target group and in the implementation of the tasks of the implementing organization, especially e-warung agents and program assistants.